Distinguishing two isomers of Nd@C82 by scanning tunneling microscopy and density functional theory - Leigh, D; Owen, J; Lee, S; Porfyrakis, K; Ardavan, A; Dennis, T; Pettifor, D; Briggs, G (2005)
Two different structural isomers of Nd@C82 have been isolated using two-stage high-performance liquid chromatography. Their molecular orbital structures have been studied by a combination of scanning tunneling microscopy (STM) and density functional theory (DFT). Matching filled and empty-states STM images to DFT calculations allowed us to distinguish directly between the two isomers on the surface. © 2005 Elsevier B.V. All rights reserved.